Sei sulla pagina 1di 93

H 0 (X) H 0 (X) H 1 (X) π 0 (X)

X G(X) f : X Y f : G(X) G(Y ) f : G(Y ) G(X)

H 0 (X) H 0 (X) H 1 (X) π 0 (X)

X G(X) f : X Y f : G(X) G(Y ) f : G(Y ) G(X)

H 0 (X) H 0 (X) H 1 (X) π 0 (X)

 R f r ϕ(x) ϕ| S 1 S 1 X P Q X P Q

 H 0 (X) π 0 (X) H 0 (X) H 0 (X) π 0 (X) H 0 (X) H 1 (X) S 1 R S 1 S 1

H 0 (X) π 0 (X) H 0 (X) H 1 (X) R S 1 S 1 S 1 H 1 (X)

X ̸= X τ X

 ∅ ∈ τ X ∈ τ A 1 , A 2 , , A n ∈ τ A 1 ∩ ··· ∩ A n ∈ τ

{A λ } λL τ λ A λ τ.

τ X (X, τ )

(M, d) a r

M

D(a, r) := {x M

U (a, r) := {x M

: d(x, a) < r}

a r

M

: d(x, a) r}

(M, d) M M

Y (X, τ ) τ Y := {A Y, A τ } Y X (Y, τ Y ) (X, τ )

W X X x W

A τ

x A W

(X, d) W X x W ϵ > 0 U (x, ϵ) W

U x X W

X x W

Y X A X

U

Y

Y

X A X

X F X X X F X

X

X X

{F λ } λ X λ F λ X

F 1 ,

, F n

X

F 1 ∪ ··· ∪ F n X

Y X

A = F Y F X

A Y

Y X A Y A X

Y X x Y Y U X x Y

x U

Y (Y ) (Y ) X

Y X x X Y U X x U Y ̸= U X x U Y x x Y

Y x, y Y x ̸= y U x V y x y U x V y =

Y

(X, d) (Y, d ) f :

X Y

Y U (x, δ) X f (U (x, δ)) U (f (x), ϵ)

f : X Y

x X U (f (x), ϵ)

x X

f : X Y

f U Y f (U )

X

f X Y

X

f f 1 : Y

f f f 1 f

(X, d) (Y, d )

f : X Y f (U )

U Y X x f (U ) f (x) U ϵ > 0 U (f (x), ϵ) U f x

U (x, δ) X f (U (x, δ)) U (f (x), ϵ)

U (x, δ) f (U (f (x), ϵ)) f (U (f (x), ϵ))

x X f x U (f (x), ϵ) Y f (U (f (x), ϵ)) X x δ > 0 U (x, δ) f (U (f (x), ϵ)) f (U (x, δ)) U (f (x), ϵ)

f : X Y F Y f (F ) X

f : X Y x X

N Y

f (x) f (N ) X x

f : X Y f U X f (U ) Y

f : X Y f f

X = A B A B

f

h : X Y

: A Y

g : B Y

f | AB g| AB

h(x) = { f (x), g(x),

x A x B

C Y h (C) = f (C) g (C) f g f (C) g (C) A B A B X f (C) g (C) X h

X X {U α } αL X = U α L

{U α } αL X

X X

X X

X = U α

U α X

X = U α 1 U α 2 ∪ ··· ∪ U α n α i L

X S X S

X U α U α X S X

X S X X = U α (X S) X

X = U α 1 U α 2 ∪ ··· ∪ U α n (X S)

S

S U α 1 U α 2 ∪ ··· ∪ U α n

X K X

x X K

U y V x y U y x V x V x U y =

K yK U y K K U y 1 U y 2 ∪· · ·∪U y n

V x 1 , V x 2 ,

, V x n V = V x 1 V x 2 ∪···∪

y

K x

̸=

y

X

V x n V X V K = x V X K

X K X K X

X R n

X X R n X U (0, m) m > 0

(X U (0, m)) = X.

m>0

X

, m k ) X U (0, N )

X X X U (0, N ) X C |x i | ≤ N i X C C X

m 1 , m 2 ,

, m k N = (m 1 , m 2 ,

C R n

U α = C U α C C C 2 n C

α 1 , α 2 ,

C U α 1 ∪ ··· ∪ U α k

C U α i C C C 1

C 1 2 n

, α k

C C 1 C 2 ⊃ ··· ⊃ C r C r+1 ⊃ ···

r C r 2 r

C α 1 ,

α n , β n C n α n

1 2 (β n α n )

β n ξ 1 ξ i

P = (ξ 1 ,

P U α U α

ε > 0 d(P, Q) < ε Q U α C δ C n 2 n δ n 2 n δ < ε

Q C n

d(P, Q) 2 n δ < ε

Q

β n+1 α n+1 =

, α k C r U α 1 ∪ ··· ∪ U α k

, ξ n ) C r

U α C n

U α

C n

 C

f : X Y X

Y

f f (V α )

X α L X = αL f (V α ) X X =

f (V α 1 ) f (V α 2 ) ∪ ··· ∪ f (V α n ) α i L

Y

Y

= f(X) = f(f (V α 1 )) f (f (V α 2 )) ∪ · · · ∪ f (f (V α n )) V α 1 V α 2 ∪ ··· ∪ V α n

f

Y = αL V α V α Y

X f : X Y f

f : X Y X Y f

X Y f : X Y f

A B R n

A

d(A, B) = inf {d(a, b) : a A, b B} > 0.

1

2 d(a, B)) : a A}

, a k A

A a A

A A A a 1 ,

{U A (a,

i (1 i k) d(a, a i ) < 1 2 d(a i , B)

d(a, B) >

1

2

d(a i , B) 1

2 min 1ik d(a i , B) = δ,

δ > 0 d(A, B) δ > 0

X X U V U V = X U V = . U V X (U, V ) X X X X X = U V U V = U V X U = V =

X X

X U X X U

=

U X = U (X U ) U = X U X U = X U =

X = U V U V X U V =

 U = X − V V V = X − U U U = ∅ U = X U = ∅ V = ∅

{0, 1} R

U = {0} V = {1} {0, 1} U V {0, 1}

U = {0, 1} ∩ ] 1

2 ,

1

2 [

V

= {0, 1} ∩ ]

1

3

2 , 2

[ .

{0, 1} R R R (U, V ) X f : X → {0, 1}

f(x) = { 0

1

x U x V

.

f S {0, 1} f (S) X {0, 1} {0} {1} {0, 1} U V X X

f : X → {0, 1}

U = f 1 {0} V = f 1 {1} U V X f

{0} {1} {0, 1}

U V = X U V = .

X X {0, 1}

[0, 1] R